Interleukin-6 and tumour necrosis factor-α cooperatively promote cell cycle regulators and proliferate rheumatoid arthritis fibroblast-like synovial cells. (3rd September 2019) - Kaneshiro, K; Sakai, Y; Suzuki, K; Uchida, K; Tateishi, K; Terashima, Y; Kawasaki, Y; Shibanuma, N; Yoshida, K; Hashiramoto, A
Abstract : Objective : To elucidate the roles of interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) in cell cycle regulation and proliferation of rheumatoid arthritis fibroblast-like synovial cells (RA-FLSs). Methods : Under stimulation with IL-6/soluble interleukin-6 receptor (sIL-6R) and TNF-α, we examined the expression of cell cycle regulators [p16 INK4a, p21 Cip1, p27 Kip1, cyclin-dependent kinase-4 (CDK4), CDK6, Cyclin D, Cyclin E, and retinoblastoma protein (pRB)] by quantitative polymerase chain reaction, Western blotting, and immunofluorescence staining. The expression of pRB, with or without 10% foetal bovine serum, was examined by Western blotting. DNA synthesis and cell viability were examined by the BrdU assay and WST-8 assay, respectively. After transfection with siRNA/ p16 INK4a, siRNA/ p21 Cip1, siRNA/ p27 Kip1, siRNA/ CDK4, or siRNA/ CDK6, RA-FLSs were successively stimulated with or without IL-6/sIL-6R or TNF-α to determine cell viability. Results : IL-6/sIL-6R significantly decreased the expression of p16 INK4a, and increased p21 Cip1, Cyclin E1, CYCLIN D, and pRB. TNF-α decreased the expression of CDK4, and significantly increased p27 Kip1, CDK6, Cyclin E1/E2, CYCLIN D, CYCLIN E, pRB, and phosphorylated pRB (phospho-pRB). By immunofluorescence staining, CYCLIN D and phospho-pRB were simultaneously stained in the single cell. In serum-free culture, the expression of pRB was apparently decreased. DNA synthesis and cell viability were significantly increased by IL-6/sIL-6R and TNF-α. Silencing of CDK6 attenuated the cell viability induced by IL-6 and TNF-α. Conclusion : The results indicate that IL-6 and TNF-α interact with each other in regulating the cell cycle and accelerate the proliferation of RA-FLSs.